2019
DOI: 10.3390/toxins11100574
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Seasonal Variations of Aflatoxin M1 in Milk from Punjab, Pakistan

Abstract: The manifestation of aflatoxins in feed and food is a major issue in the world as its presence leads to some health problems. This study investigates the incidence of aflatoxin M1 (AFM1) contamination in raw milk samples which were collected from Punjab, Pakistan. The Cluster Random Sampling technique was used to collect 960 milk samples from five different regions, and samples were collected every month. The AFM1 level in raw milk was analyzed by the ELISA technique. The findings demonstrate that 70% of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…Moreover 100% of samples analyzed in Iran during the winter had the highest concentrations of AFM1 [ 43 ], and in a meta-analysis study of 77 cases, it was also determined that the highest levels were in winter [ 33 ]. This conclusion is also corroborated by a study in Punjab-Pakistan, where the highest mean (0.875 μg/kg) was found in winter [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover 100% of samples analyzed in Iran during the winter had the highest concentrations of AFM1 [ 43 ], and in a meta-analysis study of 77 cases, it was also determined that the highest levels were in winter [ 33 ]. This conclusion is also corroborated by a study in Punjab-Pakistan, where the highest mean (0.875 μg/kg) was found in winter [ 35 ].…”
Section: Discussionsupporting
confidence: 78%
“…In India, 20.67% of 150 samples contained levels above the MRL of local legislation, being 0.5 μg/kg [ 34 ]. In Punjab-Pakistan, 70% of 690 raw milk samples were above the MRL of 0.5 μg/kg [ 35 ]. In Canakkale-Turkia, 3.3% of 120 samples exceeded local limits [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, seasonal variation has a strong impact on aflatoxin contamination in dairy products. Previous studies show that AFM1 concentrations are significantly higher in dairy samples collected in winter that those collected in summer (Akbar et al, 2019; Asi, Iqbal, Ariño, & Hussain, 2012; Bahrami et al, 2016a; Tajkarimi et al, 2008). Since it is less likely for lactating animals to have access to fresh forage, they are fed with higher amounts of stored cereals, thereby increasing the risk of AFs contamination in winter (Bahrami, Shahbazi, & Nikousefat, 2016b; Mahmoudi & Norian, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to these studies, Aslam et al (2016) found 87% of milk samples to exceed the 500 ng/L limit in three districts of Punjab province. Likewise, Akbar et al (2019) found 69% milk samples from different regions of the Punjab province to exceed the allowed limit. In one study, mean AFM 1 contamination in Lahore city was found to be as high as 17,380 ng/L with 81% samples exceeding the 500 ng/L limit.…”
Section: Introductionmentioning
confidence: 99%